Human liver chimeric mice provide a model for hepatitis B and C virus infection and treatment - Bissig, Karl-Dimiter; Wieland, Stefan F.; Tran, Phu; Isogawa, Masanori; Le, Tam T.; Chisari, Francis V.; Verma, Inder M. (The Journal of clinical investigation, 2010)
A paucity of versatile small animal models of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection has been an impediment to both furthering understanding of virus biology and testing antiviral therapies. We recently described a regulatable system for repopulating the liver of immunodeficient mice (specifically mice lacking fumaryl acetoacetate hydrolase [Fah], recombination activating gene 2 [Rag2], and the gamma-chain of the receptor for IL-2 [Il-2rgamma]) with human hepatocytes. Here we have shown that a high transplantation dose (3 x 106 to 5 x 106 human hepatocytes/mouse) generates a higher rate of liver chimerism than was previously obtained in these mice, up to 95% human hepatocyte chimerism. Mice with a high level of human liver chimerism propagated both HBV and HCV, and the HCV-infected mice were responsive to antiviral treatment. This human liver chimeric mouse model will expand the experimental possibilities for studying HBV and HCV infection, and possibly other human hepatotropic pathogens, and prove useful for antiviral drug testing.